POLA TUTURAN DALAM DIALOG PADA WEB DRAMA KOREA MELMOMANCE SEASON 1, 2, DAN 3 : SPEECH PATTERNS IN DIALOGUES IN THE KOREAN WEB DRAMA MELMOMANCE SEASONS 1, 2, AND 3 - Astrid Ananda; Usman; Tuti Wijayanti (Study Program of Indonesian Language Education, Faculty of Languages and Literature, Universitas Negeri Makassar, 2026)
This study is a qualitative descriptive study aimed at describing the patterns and functions of speech in the dialogues of the Korean web drama Melmomance, seasons 1, 2 and 3. The data in this study consist of vocabulary, phrases and sentences found in the dialogues of the Korean web drama Melmomance, seasons 1, 2 and 3. The data sources that form the subject of this study are the characters or participants in the dialogue of the Korean web drama Melmomance, seasons 1, 2, and 3. Data collection was carried out using the non-participatory observation technique. The results of this study show that there are eight speech pattern forms in the dialogues of the Korean web drama Melmomance, seasons 1, 2, and 3, namely: Greeting-greeting patterns; Call-response patterns; Information request-information provision patterns; Complaint-acknowledgement patterns; Request-permission patterns; Offer-acceptance patterns; Offer-rejection patterns; and; Question-answer patterns. Furthermore, the functions of these speech patterns in the dialogues of the Korean web drama Melmomance, seasons 1, 2, and 3, comprise five functions: Efficiency; Politeness; Awareness; Openness function, and; Cohesion function